Delaying embryo development by storing at 4°C for synchronization to recipients in microinjection technique in rabbits. (January 2013) - Nishijima, K; Liu, E; Yamaguchi, S; Tanaka, M; Morimoto, M; Watanabe, T; Fan, J; Kitajima, S
Short-term storage of embryos at low temperature induces developmental arrest of the embryo and would appear to be a valuable aid in embryo-transfer techniques to avoid wasting embryos. Embryo storage at 4°C was examined to allow synchronization with embryo-transfer recipients using the microinjection technique. Superovulation was induced in female Japanese White donor rabbits four days before mating with males. At the same time, control recipients were injected with human chorionic gonadotropin (hCG) to allow synchronization (R1); the hCG injections were delayed by 24 h in the experimental group (R2). DNA constructs for expressing human C-reactive protein or apolipoprotein AII were microinjected into the male pronuclei of the ova. The microinjected embryos were immediately transferred to recipients (R1) or stored at 4°C in phosphate-buffered saline containing 10% fetal bovine serum. After 17–20 h, the stored embryos were incubated at 37°C for one hour, and the morphologically normal embryos were transferred to recipients (R2). In the R1 rabbits, 855 embryos were transferred to 29 recipients, and 72.4% of the recipients became pregnant. Seven of the 84 offspring were transgenic. In the R2 rabbits, 478 embryos were transferred to 16 recipients, and 62.5% of the recipients became pregnant. Two of the 39 offspring were transgenic. There were no differences in pregnancy rate, litter size and transgenic integration rate between R1 and R2. These results suggest that the short-term 4°C storage of microinjected embryos can be a valuable method for synchronization with recipients, and reducing wastage of embryos and the sacrifice of rabbits.